Epidemiology of viral infections among children undergoing hematopoietic stem cell transplant: Α prospective single‐center study. Issue 4 (2nd May 2019) - Tsoumakas, Konstantinos; Giamaiou, Konstantina; Goussetis, Evgenios; Graphakos, Stelios; Kossyvakis, Athanasios; Horefti, Elina; Mentis, Andreas; Elefsiniotis, Ioannis; Pavlopoulou, Ioanna D.
Abstract: Background: Viral infections are a significant cause of morbidity and mortality in pediatric transplant populations. We analyzed the epidemiology of viral infections in pediatric hematopoietic stem cell transplant (HSCT) patients, including their incidence, associated risk factors, and outcome. Methods: In a prospective study from September 2011 to September 2015, blood, urine, and stool specimens were monitored weekly from transplantation to day 100 or after if clinically suspected, by use of real‐time polymerase chain reaction. Cytomegalovirus (CMV), Epstein‐Barr virus (EBV), BK polyomavirus (BKV), Herpes simplex virus‐1, 2, Varicella zoster virus, Human herpes virus‐6, 7, and Adenovirus infections were monitored. All children and adolescents who underwent HSCT received long‐term follow up in the regular outpatient clinics (range 2‐48 months). Results: A total of 192 HSCTs (autologous/allogeneic: 53/139) were performed in 165 subjects (median age: 5.6 years). Viruses most commonly isolated were CMV (46.1%), BKV (25.9%) and EBV (22.6%) and were more frequent in allogeneic versus autologous transplants ( P  < 0.05). Almost all high‐risk allogeneic recipients developed EBV infections post‐HSCT. EBV‐PTLD was the only cause of death among those who developed viral disease. The factors significantly associated with the development of viral infections were recipient's advanced age, unrelated donor, mismatched graft and use of peripheral blood stem cells grafts. Conclusions: Viral infections were common among our pediatric recipients. Data suggest that monitoring of viral load may be significant to the prevention of viral disease. Particular demographic and transplantation characteristics were associated with the development of viral infections post‐HSCT.